2023
DOI: 10.1111/1750-3841.16779
|View full text |Cite
|
Sign up to set email alerts
|

Watermelon (Citrullus lanatus) rind flour: Development and characterization of a novel watermelon byproduct

Caroline Abreu Pires,
Letícia São Paulo de Oliveira Cavalcante,
Allan Alexandre Martins de Carvalho
et al.

Abstract: Watermelon (Citrullus lanatus) is a fruit widely consumed by the Brazilian population; however, its rind is usually discarded, despite its nutritional value. This work aimed to develop a watermelon rind flour (WRF) and a fiber‐rich bread. The WRF was submitted to microbiological analysis, proximate composition, antioxidant activity, and a profile of phenolic compounds. Six types of bread were developed: three using WRF (20%, 30%, and 40% of wheat flour replacement) and three control samples (only wheat flour),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…It can be noted that the larger the particle size of watermelon rind powder, the more the antioxidant contents and activities released from the fortified pasta in the oral, gastric and intestinal phases of the in vitro digestion. It has been reported that many phenolic compounds in watermelon rind bind to dietary fibre in the plant cell wall ( 49 ) and could be released during human digestion ( 29 ). The bioaccessibility of total phenols and predicted glycaemic index of all pasta samples are shown in Fig 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It can be noted that the larger the particle size of watermelon rind powder, the more the antioxidant contents and activities released from the fortified pasta in the oral, gastric and intestinal phases of the in vitro digestion. It has been reported that many phenolic compounds in watermelon rind bind to dietary fibre in the plant cell wall ( 49 ) and could be released during human digestion ( 29 ). The bioaccessibility of total phenols and predicted glycaemic index of all pasta samples are shown in Fig 2 .…”
Section: Resultsmentioning
confidence: 99%